Medium effects in the pion-pole mechanism [gamma gamma ->pi(0)->nu(R)(nu)over-bar(L)(nu(L)(nu)over-bar(R))] of neutron star cooling - Arretche, F. [UNESP]; Natale, A. A. [UNESP]; Voskresensky, D. N. (American Physical Soc, 2003)
Nuclear medium effects in the neutrino cooling of neutron stars through the reaction channel γγ→π0 →ν Rν̄L(νLν̄R) are incorporated. Throughout the paper we discuss different possibilities of right-handed neutrinos, massive left-handed neutrinos, and standard massless left-handed neutrinos (reaction is then allowed only with medium modified vertices). It is demonstrated that multiparticle effects suppress the rate of this reaction channel in the dense hadron matter by 6-7 orders of magnitude that does not allow to decrease existing experimental upper limit on the corresponding π0νν̄ coupling. Other possibilities of the manifestation of the given reaction channel in different physical situations, e.g., in the quark color superconducting cores of the most massive neutron stars, are also discussed. We demonstrate that in the color-flavor-locked superconducting phase for temperatures T≲ 0.1-10 MeV (depending on the effective pion mass and the decay width) the process is feasibly the most efficient neutrino cooling process, although the absolute value of the reaction rate is rather small.